Implementation of Criminal Law in Narcotics Cases in Indonesia - Clarissa (Journal of Strafvordering Indonesian, 2024)
Issues related to drug-related crimes have become a major concern around the world and an ongoing topic of discussion at the national and international levels. The problem of drug abuse is not only a national, but also a global challenge that is troubling various nations. The adverse effects of drug abuse involve damage to physical, mental health, emotional, and societal values. Narcotics abuse has become a serious threat faced by society and the nation, forming a national and international organized crime. With this background, it raises a topic entitled "The Application Of Narcotic Penal Law In Indonesia". Which reviews how criminal law is used to regulate narcotics crimes in Indonesia, including the criminal law system applied. The research method applied in this journal is a normative juridical approach, in which the author analyzes the problem by considering legal principles and referring to legal norms in legislation. The data used in this scientific journal is secondary.